Clinico-Etiological Profile and Outcome of Neonatal Seizures - A Hospital-Based Cross-Sectional Study in Western Nepal - Nagendra Chaudhary; Astha Paudel; Dinesh Chaudhary; Binod Kumar Gupta (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Neonatal seizure, a common problem encountered in neonatal intensive care unit (NICU) setting, is an important determinant of outcome of neurological disorders in newborn period. The aim of the study was to study the clinical and etiological proﬁle of neonatal seizures along with their outcomes. MATERIAL AND METHODS A prospective observational study was conducted in the NICU of Department of Pediatrics at Universal College of Medical Sciences, Bhairahawa, Nepal from November 2019 to March 2021. Babies with neonatal seizures were enrolled in the study after obtaining written consent from parents. RESULTS Out of 870 admitted neonates, 9.7% (n=85) developed clinical seizures where 62.4% were males. Most cases (87.1%) had seizures within 48-hour of life with subtle seizures (92.9%) being the commonest. About 43.5% cases had single episode of seizure followed by multiple episodes. Perinatal asphyxia (92.9%) either alone and/or associated with hypocalcemia (80%) followed by sepsis (40%) and hyponatremia (18.8%) were common etiologies for neonatal seizures. Most of the seizures (76.5%) were aborted with use of single anti-epileptic drug. About 86% (n=73) survived and rest expired. CONCLUSION Subtle seizures were common and perinatal asphyxia was the predominant etiology for neonatal seizures. Thus, strengthening the healthcare facility during delivery of the newborn, proper newborn care and nutrition must be emphasized to decrease the incidence of seizures in developing nations like Nepal.